Implementation of Activity-Based Language Week Program in Improving Arabic Communication Skills at Ma’had al-Jami’ah - Tribhuwan Kumar; Irsal Amin; Mahyudin Ritonga; Sobhan Sobhan (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2022)
Improving Arabic speaking skills for non-native speakers are faced with serious problems, so educational institutions must be able to make new breakthroughs in efforts to improve communication skills. Ma'had al-Jami'ah IAIN Padangsidimpuan determines that a program is seen as part of efforts to improve Arabic communication skills, namely